The agony and the ecstasy [videorecording (DVD)] - Reed, Carol, 1906-1976; Heston, Charlton; Harrison, Rex; Cilento, Diane; Stone, Irving, 1903-1989 (Studio classic., 2014)
Despite the grueling physical demands involved, renowned Renaissance artist Michelangelo spends more than four years creating the Sistine Chapel's spectacular ceiling fresco. All the while, he questions his own religious views and battles with the man who commissioned him, Pope Julius II.